HUBUNGAN KARAKTERISTIK DAN PAPARAN INFORMASI RESIKO PENYAKIT GIGI IBU MENOPAUSE TERHADAP PRILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA IBU MENOPAUSE DI KABUPATEN LABUHANBATU UTARA - Intan Aritonang; Asmawati; Cut Aja Nuraskin (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Menopause is a normal process in every woman's life. Women can be declared menopause if they have not menstrual cycles for at least 12 months because of ovarian activityhad stop. Estrogen is a steroid hormone that has receptors in the salivary glands and oral mucosa which more important in maintaining bone homeostasis including the jawbone, the mouth will be occur, decrease in jaw bone density and periodontal disease. Health behavior is influenced by individual and environmental factors. This study to determine the relationship between the characteristics and information exposure about dental desease risk at post-menopausal to women behavior about dental health care at menopausal women in Labuhan Batu Utara Regency. This study uses quantitative research methods because the population is large enough. This study was conducted to analyze whether there is a relationship between the independent variable and the dependent variable used a cross sectional approach. Univariate analysis to determine the description of women characteristics and information exposure and dental health care behavior of postmenopausal women. Bivariate analysis to determine the relationship between women characteristics and information exposure on the behavior of postmenopausal women in Labuhan Batu Utara Regency. Bivariate analysis was carried out with the Chi-Square Statistical Test where the independent variable and the dependent variable were both on the categorical scale, the ordinal scale. The results of statistical test Mann Whitney showed that there was a significant relationship between Menopause Status (p = 0.014), Education Level (p = 0.001), Family Income (p = 0.007) and Information Exposure (p = 0.004) with Women Behavior about dental health and mouth care during menopause.